Pandemic pedagogy : preparedness in uncertain times - Sengupta, Enakshi (Emerald Publishing Limited, 2023)
The COVID-19 pandemic has impacted over a billion students, resulting in a mass transition to online education and the cancellation or postponement of countless seminars, workshops, exams, sports events and conferences. While remote learning has allowed institutions to continue providing education to students throughout these circumstances, it has also created a number of challenges for the mental health of both faculty and students as well as to the technical capabilities of higher education institutions. At the start of the pandemic, not every university had the necessary facilities for the quick switch to remote learning, not all faculty were prepared to make it and not all students were equipped to take on more responsibility for their learning. Pandemic Pedagogy: Preparedness in Uncertain Times collates various case studies and other empirical research that examine learning practices and demonstrate approaches to address future catastrophes and continue the pandemic recovery process. Contributors discuss both theoretical models and strategic frameworks currently in use, as well as the benefits they provide, helping institutions address student and faculty concerns and prioritise future preparedness. Designing an adaptable education system capable of dealing with future crises, Pandemic Pedagogy: Preparedness in Uncertain Times will benefit educators, leaders, policy makers, government organizations, university faculty members and students.
Keywords: College teaching.; COVID-19 Pandemic, 2020- -- Influence.; Education -- Teaching / Methods & Strategies.; Teaching skills & techniques.; elektronické knihy; electronic books